2022
DOI: 10.1530/eje-21-0865
|View full text |Cite
|
Sign up to set email alerts
|

The glucagon receptor antagonist LY2409021 has no effect on postprandial glucose in type 2 diabetes

Abstract: Objective: Type 2 diabetes (T2D) pathophysiology includes fasting and postprandial hyperglucagonemia, which has been linked to hyperglycemia via increased endogenous glucose production (EGP). We used a glucagon receptor antagonist (LY2409021) and stable isotope tracer infusions to investigate consequences of hyperglucagonemia in type 2 diabetes. Design: A double-blinded, randomized, placebo-controlled crossover study was conducted. Methods: Ten patients with T2D and ten matched non-diabetic controls underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…However, the glucose-lowering efficacy tailed off with higher doses (30 mg, 60 mg qd) [ 94 ]. This is consistent with the observation that the same compound (100 mg) given as a single dose, demonstrated no improvement in glucose tolerance in patients with T2DM [ 95 ]. Mechanistic studies further confirmed that though being glucotropic, glucagon is also a potent insulinotropic hormone with antidiabetic potential [ 96 ].…”
Section: Incretin-based Medicationssupporting
confidence: 92%
“…However, the glucose-lowering efficacy tailed off with higher doses (30 mg, 60 mg qd) [ 94 ]. This is consistent with the observation that the same compound (100 mg) given as a single dose, demonstrated no improvement in glucose tolerance in patients with T2DM [ 95 ]. Mechanistic studies further confirmed that though being glucotropic, glucagon is also a potent insulinotropic hormone with antidiabetic potential [ 96 ].…”
Section: Incretin-based Medicationssupporting
confidence: 92%
“…Further clinical development of GRAs was hampered by long‐term adverse events such as increased BW, liver fat content, systolic blood pressure, LDL‐cholesterol, and transaminase levels, associated with α‐cells hyperplasia and severe hypoglycaemia 131,134 . Also, GRA LY2409021 did not improve PPG following a mixed meal test 135 and paradoxically reduced glucose tolerance following an oral glucose tolerance test without restoring the incretin effect compared to placebo in 10 T2D patients 136 . GCGR antagonism was associated with stable fasting insulin levels, despite the amelioration of glucose control, and increased insulin levels during oral glucose tolerance test with a subsequent greater post‐load decrease in glucose, suggesting improved insulin sensitivity both in the fasting and fed states 134 .…”
Section: Use Of Glucagon In Type 2 Diabetes Therapymentioning
confidence: 99%